Місце України на світовому ринку послуг - Краснодєд, Тетяна Леонідівна; Краснодед, Татьяна Леонидовна; Krasnodied, Tetiana; Попова, Тетяна Вікторівна; Попова, Татьяна Викторовна; Popova, Tetiana (My University, 2019)
UK: У статті висвітлено необхідність та актуальність дослідження сучасного світового ринку послуг, що зумовлено швидким розвитком даної галузі в контексті народногосподарського комплексу країни. У контексті вивчення даної проблеми виявлено місце України на ньому. Проаналізовано показники, які характеризують стан зовнішньої торгівлі України послугами. Аналіз являє собою дослідження тих самих основних показників, що використовуються під час дослідження зовнішньої торгівлі товарами. Проаналізовано експортну та імпортну структуру послуг України. Виявлено напрями експортноорієнтованості та імпортозалежності у сфері послуг. Виявлено регіони України, які характеризуються найвищим рівнем розвитку, ступенем активності та участі в її зовнішньоторговельній діяльності, і навпаки. RU: В статье освещены необходимость и актуальность исследования современного мирового рынка услуг, обусловленные быстрым развитием данной отрасли в контексте народнохозяйственного комплекса страны. В контексте изучения данной проблемы обнаружено место Украины на нем. Проанализированы показатели, характеризующие состояние внешней торговли Украины услугами. Анализ представляет собой исследование тех же самых основных показателей, используемых при исследовании внешней торговли товарами. Проанализирована экспортная и импортная структура услуг Украины. Выявлены направления експортноориентованости и импортозависимости в сфере услуг. В процессе анализа выявлены регионы Украины, характеризующиеся высоким уровнем развития, степенью активности и участием в ее внешнеторговой деятельности, и наоборот. EN: The paper highlights the necessity and relevance of the research on the world market services, which is influenced by the rapid development of this sector as a part of national economy. Issues of export and import orientation of Ukraine on the world service market and European market are of great concern to many researchers. The results of the study will have implications for helping the Government devise sound development policies for strengthening export potential of Ukraine on the world market services. The indicators characterizing the state of foreign trade of Ukrainian services werecalculated and analyzed: volumes of export and import of services, trade balance, indicators of export cover ratio, structure of imports and exports of services, the share of the country in the total volume of foreign trade and some others.Analysis of foreign trade of Ukraine services was carried out by the use of the same basic indicators as in the sector of goods foreign trade. Therefore, in the paper, a comparative analysis of export and import indicators of Ukraine by categories "goods" and "services" was conducted. The position of Ukraine on the world market of services concerning CIS countries and the European Union was also revealed. The analysis determines the directions of export orientation and import dependence of our country in the sector of services. According to the export and import indicators advantageous categories of provided and received services were determined. Also the list of economically developed regions of Ukraine, characterized by the highest level of their participation in the foreign trade activities, was defined. It was revealed that the low level of economic development of certain regions resultswas connected with a small number of exporting and importing companies, which did not contribute to the promotion of Ukraine on the world market of goods and services. Thus, today Ukraine suffers the lack of stability in exports and imports of services, but dynamically uses its potential in order to strengthen its position on the world market. Ukraine already has considerable achievements are certain in the world market of services and tries swiftly to develop this experience.
Place of Ukraine on the world service market
Keywords: зовнішня торгівля; послуги; світовий ринок; експорт; імпорт; структура послуг; зовнішньоторговельний баланс; торгове сальдо; внешняя торговля; услуги; мировой рынок; экспорт; импорт; структура услуг; внешнеторговый баланс; торговое сальдо; foreign trade; services; world market; export; import; service structure; foreign trade balance